Preparation method and application of multi-component SEI film

Through the multi-component SEI film preparation method, the synergistic effect of specific polymer matrix, lithium salt and additives, combined with the ultraviolet lamp irradiation process, the problem of insufficient performance of traditional SEI films is solved, and efficient, stable and uniform SEI film preparation is achieved, which significantly improves battery performance and reduces production costs.

CN119601594APending Publication Date: 2025-03-11CHINA RAILWAY SEVENTH GROUP FIFTH ENGINEERING CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411661231.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Traditional SEI films have problems such as low ion conductivity, uneven distribution, insufficient mechanical properties, complex preparation process and high cost, which affect the charging and discharging efficiency, cycle life and safety of the battery.

Method used

The multi-component SEI film preparation method is adopted to optimize the mass ratio by selecting polymer matrix, lithium salts and a variety of additives (such as fluoride, oxide, boride, phosphide and carbide), and scraping or spin coating process is carried out under ultraviolet lamp irradiation to form a dense and uniform SEI film.

Benefits of technology

It significantly improves the ion conductivity, stability and uniformity of the SEI film, improves the charging and discharging efficiency, cycle life and safety of the battery, simplifies the preparation process, reduces production costs, and is suitable for large-scale commercial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601594A_ABST
    Figure CN119601594A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of material chemical engineering, and particularly relates to a preparation method and application of a multi-component SEI (solid electrolyte interface) film. Various substances are carefully screened to form a multi-component system, and an accurate mass ratio is determined; due to the combination, all the components have a synergistic effect, and the comprehensive performance of the SEI film is remarkably improved; operation is performed in a glove box with low water oxygen content, so that the raw materials are pure; the material can be widely applied to various batteries such as electric vehicles and energy storage batteries to improve the charge-discharge efficiency, stability and cycle life of the batteries, and provides powerful support for the technical progress of the batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a method for preparing a multi-component solid electrolyte interface (SEI) film and application thereof in batteries. Background Art

[0002] In the development of modern science and technology, electrochemical energy storage systems such as lithium batteries play a vital role and have irreplaceable significance in promoting global energy transformation and achieving sustainable development goals. The SEI film naturally formed on the surface of the negative electrode of the battery is generated by the chemical reaction between the electrolyte / solid electrolyte and the negative electrode material during the first charge and discharge process of the battery, which has a key impact on battery performance in many aspects.

[0003] On the one hand, the SEI membrane can act as a physical barrier between the electrode and the electrolyte / solid electrolyte, effectively preventing the electrolyte / solid electrolyte from further reacting with the negative electrode material, thereby reducing the unnecessary loss of active materials in the battery, and plays an important role in maintaining the capacity of the battery. On the other hand, it also determines the key performance indicators of the battery such as cycle life, rate performance and safety to a certain extent. However, the traditional SEI membrane has many limitations. Its ion conductivity is relatively low, which directly leads to an increase in the internal resistance of the battery, which in turn affects the charge and discharge efficiency of the battery. During the charge and discharge process of the battery, lithium ions need to shuttle quickly between the positive and negative electrodes, and the SEI membrane with low ion conductivity will hinder this process, slowing down the charge and discharge speed of the battery and reducing its performance.

[0004] The uneven distribution of the SEI film is also a serious problem. This unevenness will cause uneven deposition of lithium ions on the electrode surface, which can easily lead to the growth of lithium dendrites. The presence of lithium dendrites will not only destroy the integrity of the SEI film, allowing more electrolyte / solid electrolyte to contact and react with the negative electrode material, accelerating the decay of battery capacity, but also the sharp lithium dendrites may pierce the diaphragm, causing a short circuit between the positive and negative electrodes, causing thermal runaway inside the battery, seriously endangering the safety of the battery, and may even cause serious consequences such as fire or explosion.

[0005] In addition, the electrode material will inevitably undergo volume expansion and contraction during battery charging and discharging, which places high demands on the mechanical properties of the SEI film. If the mechanical properties of the SEI film are insufficient, the SEI film may rupture during the volume change of the electrode material, lose its protective effect, and further aggravate the deterioration of battery performance.

[0006] Existing SEI film preparation methods also have many shortcomings. Some methods are complex, involving multiple cumbersome steps and strict operating conditions, and require professional equipment and skilled technicians to operate, which not only increases production costs, but also reduces production efficiency, making it difficult to meet the needs of large-scale commercial production. For example, some preparation methods need to be carried out under high temperature, high pressure or special atmosphere conditions, which have extremely high requirements for equipment and huge equipment investment costs. In addition, the raw materials used in some preparation methods are expensive or scarce, resulting in high overall costs, which limits their wide application in actual production. Although some methods can produce SEI films with good performance under laboratory conditions, it is difficult to achieve large-scale stable production, and the consistency of product quality is difficult to guarantee.

[0007] At present, the technical improvement directions for SEI membranes are mainly concentrated in several aspects. Controlling charging conditions is a common method, which attempts to improve the formation process of SEI membranes by optimizing parameters such as charging current, voltage and time. However, the effect of this method is often limited, because the chemical reactions inside the battery are complex, and it is difficult to fundamentally solve all the problems of SEI membranes by adjusting the charging conditions alone. Introducing an artificial SEI layer is another attempt, which simulates the function of the SEI membrane by pre-coating a layer of artificial synthetic materials on the surface of the negative electrode. However, this method faces the challenges of how to ensure good bonding between the artificial SEI layer and the electrode material and how to ensure its stability during long-term use in actual operation. Optimizing the electrolyte / solid electrolyte formula is also one of the research hotspots, which affects the composition and performance of the SEI membrane by changing the composition and proportion of the electrolyte. However, changes in the electrolyte formula may bring other problems, such as compatibility issues with electrode materials and negative effects on the overall performance of the battery. In summary, there is an urgent need for a new SEI membrane preparation method that can effectively overcome many of the shortcomings of the existing technology, achieve a comprehensive improvement in the performance of the SEI membrane, and meet the requirements of large-scale commercial production. Summary of the invention

[0008] A method for preparing a multi-component SEI film comprises the following steps:

[0009] S1: weigh a polymer matrix and a lithium salt, wherein the polymer matrix is ​​one or more of polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP); and the lithium salt is one or more of lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), and lithium bis(fluorosulfonyl) imide (LiFSI); dissolve them in a solvent, and heat and stir for 6-24 hours to obtain a mixed solution, wherein the solvent is one or more of acetonitrile, N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), ethanol, acetone, and ethylene glycol;

[0010] S2. Weigh fluoride, oxide, boride, phosphide and carbide in a glove box, wherein the fluoride is one or more of LiF, NaF, KF, ZnF2, LiPF6 and LiBF4, the oxide is one or more of Li2O, SiO2, Al2O3, TiO2 and CeO2, the boride is one or more of LiBH4, C4BLiO8, TiB2, BN and H3BO3, the phosphide is one or more of LiPO2F2, Zn3P2, LiPF6, Zn3P2, AlP, Cu3P2, Li3PO4 and SiP, the carbide is one or more of Li2CO3, TiC, SiC and B4C, continue heating and stirring in the above mixed solution for 6-24h to obtain a SEI film solution;

[0011] S3, under ultraviolet light, the SEI film solution is evenly scraped on the substrate with a scraper, or evenly spin-coated on the substrate by setting a rotation speed to obtain a SEI film to be dried, and then transferred to a vacuum drying oven to dry to obtain a SEI film;

[0012] S4: scraping or spin coating the mixed solution of S1 on the substrate according to the method of step (3), and then transferring it to a vacuum drying oven and drying it to obtain a polymer solid electrolyte membrane;

[0013] S5: transferring the SEI film prepared in step (3) to the upper and lower surfaces of the polymer solid electrolyte membrane in step (4), assembling according to the battery assembly process and performing performance testing.

[0014] Furthermore, the polymer matrix is ​​preferably PVDF and PVDF-HFP.

[0015] Furthermore, the lithium salt is preferably LiTFSI and LiFSI.

[0016] Furthermore, the solvent is preferably DMF and NMP.

[0017] Furthermore, the mass ratio of the polymer matrix to the lithium salt is preferably 2:1.

[0018] Furthermore, the stirring temperature is preferably 50° C., and the stirring time is preferably 12 h.

[0019] Furthermore, the fluoride is preferably LiF, the oxide is preferably Li2O, the boride is preferably LiBH4, the phosphide is preferably LiPO2F2, the carbide is preferably Li2CO3, and the mass ratio of the fluoride, oxide, boride, phosphide and carbide is preferably 2:0.5:1:1:0.5.

[0020] Furthermore, the mass ratio of the total mass of the fluoride, oxide, boride, phosphide and carbide to the mass of the polymer matrix is ​​0.1-1.

[0021] Furthermore, the wavelength range of the ultraviolet lamp is 200-400nm, preferably 365nm, and the irradiation intensity is 5-20mW / cm 2 , preferably 10 mW / cm 2 .

[0022] On the other hand, the present invention provides a battery comprising a multi-component SEI film prepared by the method.

[0023] Beneficial technical effects of the invention:

[0024] Carefully select a variety of substances to form a multi-component system, such as a specific polymer matrix (PVDF and PVDF-HFP), lithium salts (LiTFSI and LiFSI) and various additives (fluoride LiF, etc.), and determine the precise mass ratio. This combination enables the components to synergize and significantly improve the overall performance of the SEI membrane. The components cooperate with each other, such as LiF enhancing stability and Li3P improving ion conduction, and work together on the SEI membrane to overcome the performance defects of traditional membranes. The operation is carried out in a glove box with low water and oxygen content to ensure the purity of the raw materials. At the same time, ultraviolet light irradiation (365nm, 10mW / cm 2 ) under the scraper coating (scraper height 20μm) or spin coating process to optimize the membrane structure, make it more dense and uniform, and enhance ion conductivity and stability. This process not only improves the membrane quality, but also simplifies the operation and is easy to achieve large-scale production. The SEI film thickness is precisely controlled to about 10μm, balancing the suppression of side reactions and ion transport to optimize battery performance. It is widely used in a variety of batteries, such as electric vehicles, energy storage batteries, etc., to improve their charging and discharging efficiency, stability and cycle life, providing strong support for the advancement of battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Principle flow chart.

[0026] Figure 2 The following is a surface scanning electron microscope (SEM) image of the sample prepared in the example.

[0027] Figure 3 This is a cross-sectional SEM image of the sample prepared in the example.

[0028] Figure 4 The electrochemical impedance diagrams of the samples prepared in the examples and comparative examples show that the SEI membrane in the examples has higher ion conductivity, which is beneficial to the ion transport process.

[0029] Figure 5 The linear sweep voltammograms of the samples prepared in the examples and comparative examples show that the SEI film in the examples has a wider electrochemical stability window, which is beneficial to improving the stability of the electrode-electrolyte interface.

[0030] Figure 6 The lithium symmetric cycle performance diagrams of the samples prepared in the examples and comparative examples indicate that the SEI film in the examples is conducive to promoting the formation of a stable electrode-electrolyte interface and can achieve a stable lithium deposition and stripping process. DETAILED DESCRIPTION

[0031] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0032] Example 1

[0033] The present invention aims to provide a multi-component SEI membrane with excellent ion conductivity, high uniformity and outstanding stability, so as to overcome the defects of traditional SEI membranes in these aspects, thereby significantly improving the performance of the battery. A method for preparing a multi-component SEI membrane with simple process, low cost and easy large-scale industrial production is established to solve the problems of complex process, high cost and difficulty in large-scale application of existing preparation methods. The multi-component SEI membrane is widely used in various types of batteries, including but not limited to mobile electronic communication equipment batteries, electric vehicle batteries, energy storage batteries, power batteries and energy storage power station batteries, etc., to promote the development and application of battery technology in various fields.

[0034] In a glove box filled with inert gas (such as high-purity argon) and with extremely low water and oxygen content (usually water content less than 0.1ppm, oxygen content less than 0.1ppm), accurately weigh a polymer matrix and a lithium salt in a specific mass ratio range (0.5-5):1 (optimized to 2:1). The polymer matrix can be selected from one or more of polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), among which PVDF and PVDF-HFP are preferred. The lithium salt can be selected from one or more of lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), and LiTFSI and LiFSI are optimally selected. The weighed polymer matrix and lithium salt are dissolved in a suitable solvent, which can be selected from one or more of acetonitrile, N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), ethanol, acetone, and ethylene glycol, preferably DMF and NMP. Stir at a temperature of 30-80°C (optimally 50°C) at a constant stirring speed (such as 300-800rpm, preferably 500rpm) for 6-24h (ideally 12h) to ensure that the raw materials are fully dissolved and mixed evenly to obtain a mixed solution.

[0035] Accurately weigh the fluoride, oxide, boride, phosphide and carbide according to the mass ratio of (1-5):(0-2):(0-4):(0-4):(0-2) (preferably 2:0.5:1:1:0.5). Fluorides may include one or more of LiF, NaF, KF, ZnF2, LiPF6, and LiBF4, and LiF is recommended; oxides may be selected from one or more of Li2O, SiO2, Al2O3, TiO2, and CeO2, preferably Li2O; borides may be selected from one or more of LiBH4, C4BLiO8, TiB2, BN, and H3BO3, and LiBH4 is preferred; phosphides may be one or more of LiPO2F2, Zn3P2, LiPF6, Zn3P2, AlP, Cu3P2, Li3PO4, and SiP, and LiPO2F2 is recommended; carbides may be selected from one or more of Li2CO3, TiC, SiC, and B4C, and Li2CO3 is preferred. Add these additives to the mixed solution prepared above, and continue stirring for 6-24 h (preferably 12 h) at the same temperature (30-80° C., preferably 50° C.) and stirring speed (300-800 rpm, preferably 500 rpm) until all additives are completely dissolved to obtain a uniform SEI film solution.

[0036] Under ultraviolet light (ultraviolet light wavelength range is 200-400nm, preferably 365nm, irradiation intensity is 5-20mW / cm2 , preferably 10mW / cm 2 ), the SEI film solution is scraped by precisely adjusting the scraper height (0.5-40 μm, preferably 20 μm), or the appropriate spin coating speed (500-3000 rpm, adjusted according to the required film thickness) is set to spin coat on a substrate (such as a glass substrate, a metal substrate or a polymer substrate, preferably a polyethylene terephthalate (PET) substrate) to obtain a SEI film to be dried. It is then transferred to a vacuum drying oven and dried for 6-24 hours (preferably 12 hours) at a temperature of 60-120°C (preferably 100°C) and a vacuum degree of less than 100Pa (preferably 10-50Pa) to remove the solvent and possible small molecule impurities to obtain a high-quality SEI film.

[0037] The mixed solution prepared in step 1 is treated on the substrate by the same coating method (scrape coating or spin coating) as the SEI film, and then dried under the same drying conditions (60-120°C, preferably 100°C; vacuum degree less than 100Pa, preferably 10-50Pa; drying time 6-24h, preferably 12h) to obtain a polymer solid electrolyte membrane of a certain thickness (such as 10-100μm, preferably 50μm). Finally, the prepared SEI membrane is transferred to the upper and lower surfaces of the polymer solid electrolyte membrane, and assembled into a battery according to the conventional battery assembly process (including electrode preparation, diaphragm selection, battery packaging and other steps), and a comprehensive performance test is performed.

[0038] The multi-component SEI film prepared by the above method is widely used in various types of batteries, including batteries in mobile electronic communication devices (such as smart phones, tablets, etc.), which can improve their endurance and battery life; applied to electric vehicle batteries (such as lithium-ion power batteries), it helps to improve the range, charging efficiency and safety of electric vehicles; used in energy storage batteries (such as home energy storage systems, power grid energy storage power stations, etc.), to enhance the charging and discharging performance and cycle stability of energy storage systems; used in power batteries (such as batteries for power tools, drones, etc.), can improve the battery's rate performance and overall performance; and used in batteries in large-scale energy storage power stations to ensure efficient operation and long-term stability of energy storage power stations.

[0039] Example 2

[0040] (1) In a glove box, 4.8 g of PVDF-HFP and 2.4 g of LiTFSI were weighed and added to a sample bottle containing 20 ml of DMF, and stirred at 50° C. for 12 h to allow the mixture to be fully dissolved and mixed.

[0041] (2) Weigh 0.48 g of LiF, 0.12 g of Li2O, 0.24 g of LiBH4, 0.24 g of LiPO2F2, and 0.12 g of Li2CO3 and add them to the sample bottle. Stir at 50°C for 12 h until they are completely dissolved to obtain a solution for preparing a SEI film.

[0042] (3) Under ultraviolet light irradiation conditions, most of the water vapor and air in the environment are removed. 2 ml of the SEI film solution prepared above is taken out and dropped on the glass substrate. The height of the scraper is adjusted to 20 μm. The SEI film to be dried is obtained by scraping, and then transferred to a vacuum drying oven and dried at 100°C for 12 hours to obtain a SEI film with a thickness of 10 μm.

[0043] (4) Under ultraviolet light irradiation, 10 ml of the mixed solution prepared in step (1) was taken out and dropped on a glass substrate, and the height of the scraper was adjusted to 100 μm, and the polymer solid electrolyte membrane to be dried was obtained by scraping. Then, it was transferred to a vacuum drying oven and dried at 100° C. for 12 hours to obtain a polymer solid electrolyte membrane with a thickness of 50 μm.

[0044] (5) The SEI film prepared in step 3 was transferred to the upper and lower surfaces of the polymer solid electrolyte in step 4, and was punched into discs with a diameter of 14 mm using a cutting machine. The discs were assembled into CR2025 button cells in a glove box according to the battery assembly process, and electrochemical impedance spectroscopy (EIS), linear sweep voltammetry (LSV) and lithium symmetric cycling performance tests were performed.

[0045] Comparative Example:

[0046] (1) In a glove box, 4.8 g of PVDF-HFP and 2.4 g of LiTFSI were weighed and added to a sample bottle containing 20 ml of DMF, and stirred at 50° C. for 12 h to allow the mixture to be fully dissolved and mixed.

[0047] (2) Under ultraviolet light irradiation conditions, most of the water vapor and air in the environment are removed. 10 ml of the mixed solution obtained in step (1) is taken out and dropped on a glass substrate. The height of the scraper is adjusted to 100 μm, and the polymer solid electrolyte membrane to be dried is obtained by scraping. Then it is transferred to a vacuum drying oven and dried at 100°C for 12 hours to obtain a polymer solid electrolyte membrane with a thickness of 50 μm.

[0048] (3) The polymer solid electrolyte membrane prepared in step 2 was punched into discs with a diameter of 14 mm using a cutting machine, and assembled into CR2025 button cells in a glove box according to the battery assembly process, and electrochemical impedance spectroscopy (EIS), linear sweep voltammetry (LSV) and lithium symmetric cycling performance tests were performed.

[0049] The present invention carefully selects a variety of specific additives, including fluorides, oxides, borides, phosphides and carbides, and optimizes their combination ratio. These additives are not simply mixed, but jointly improve the comprehensive performance of the SEI film through a synergistic mechanism. For example, LiF, as a stable fluoride, can form a stable fluoride phase in the SEI film, effectively improve the chemical stability of the SEI film, and prevent it from over-reacting with the electrolyte during the battery charging and discharging process. Li3P has good lithium ion conductivity. It can construct a channel in the SEI film that is conducive to lithium ion transmission, improve the ion conduction path, and reduce the resistance of ion transmission, thereby improving the ion conductivity of the SEI film. LiBH4, due to its special chemical structure, can give the SEI film a certain flexibility, so that it can better adapt to the volume change of the electrode material during the charging and discharging process, and reduce the risk of membrane rupture. LiPO2F2 not only helps to improve the ionic conductivity of the SEI film, but also enhances its electrochemical stability and inhibits the growth of lithium dendrites. Li2CO3 can act as a nucleating agent in the formation process of SEI film, which helps to form a uniform and dense film structure and further improve the uniformity of SEI film. Through the synergistic effect of these additives, the ion conductivity, stability and uniformity of SEI film are jointly improved, effectively solving the problems existing in traditional SEI film.

[0050] The introduction of ultraviolet light irradiation during the preparation of the SEI film is one of the important innovations of the present invention. Under ultraviolet light irradiation (wavelength 200-400nm, preferably 365nm, intensity 5-20mW / cm 2 , preferably 10mW / cm 2 ) is not only to remove water vapor and air in the environment, but more importantly, it has a series of positive effects on the components in the SEI membrane solution. Ultraviolet light has enough energy to excite the molecules in the solution to undergo energy level transitions, causing the breaking and reformation of certain chemical bonds, thereby changing the arrangement of molecules. Specifically, ultraviolet light irradiation may trigger chemical reactions between additive molecules and polymer matrices and between additive molecules, forming a more stable and ordered chemical bonding structure. This structural adjustment makes the final SEI membrane structure more compact and uniform, reducing defects and holes in the membrane. The dense membrane structure can more effectively prevent direct contact between the electrolyte and the negative electrode material, further improving the stability of the SEI membrane. At the same time, the uniform membrane structure contributes to the uniform transmission of lithium ions in the membrane, reduces the aggregation and deposition of lithium ions in local areas, thereby reducing the possibility of lithium dendrite formation, and further improving ion conductivity and stability.

[0051] The present invention can accurately control the thickness of the SEI film between 0.5-20 μm (preferably 10 μm), which is achieved by accurately adjusting the process parameters such as the scraper height (0.5-40 μm, preferably 20 μm) or the spin coating speed (500-3000 rpm). Within this thickness range, the SEI film can exert the best performance. When the SEI film thickness is too thin, it may not be able to completely cover the negative electrode surface, causing part of the negative electrode material to be exposed to the electrolyte, which is easy to cause side reactions and reduce the cycle life and safety of the battery. When the SEI film thickness is too thick, although it can better prevent side reactions, it will increase the resistance to lithium ion transmission, resulting in a decrease in ion conductivity and affecting the charge and discharge efficiency of the battery. By accurately controlling the film thickness to about 10 μm, the SEI film can not only effectively prevent side reactions between the electrolyte and the negative electrode material, but also ensure the rapid transmission of lithium ions in the film, thereby optimizing the battery performance and realizing the precise regulation of the SEI film performance.

[0052] The preparation method of the present invention has significant advantages. Its process is relatively simple, does not require complex equipment and cumbersome operating steps, and is easy to achieve large-scale promotion in industrial production. In terms of cost, the raw materials selected are mostly common and relatively low-priced chemicals, and no special process conditions and expensive equipment are required during the preparation process, which greatly reduces the production cost. In addition, the SEI film prepared by the present invention has excellent performance and can significantly improve the charging and discharging efficiency, stability and cycle life of the battery. In terms of charging and discharging efficiency, since the SEI film has high ion conductivity, it can accelerate the transmission speed of lithium ions and reduce the internal resistance of the battery, thereby improving the charging and discharging efficiency. In terms of stability, the synergistic effect of the stable SEI film structure and additives enables it to maintain good performance during the battery charging and discharging process and is not easily disturbed by external factors. In terms of cycle life, the uniform membrane structure and good stability help to reduce the capacity decay of the battery during the cycle process, extend the service life of the battery, and provide strong support for the development of battery technology.

Claims

1. A method for preparing a multi-component SEI film, characterized in that: The following steps are involved: S1: Weigh a polymer matrix and a lithium salt, wherein the polymer matrix is ​​one or more of polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), and the lithium salt is one or more of lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), and lithium bis(fluorosulfonyl) imide (LiFSI), dissolve them in a solvent, heat and stir for 6-24 hours to obtain a mixed solution, and the solvent is one or more of acetonitrile, N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), ethanol, acetone, and ethylene glycol; S2: Weigh fluoride, oxide, boride, phosphide and carbide in a glove box, wherein the fluoride is one or more of LiF, NaF, KF, ZnF2, LiPF6, and LiBF4, the oxide is one or more of Li2O, SiO2, Al2O3, TiO2, and CeO2, the boride is one or more of LiBH4, C4BLiO8, TiB2, BN, and H3BO3, the phosphide is one or more of LiPO2F2, Zn3P2, LiPF6, Zn3P2, AlP, Cu3P2, Li3PO4, and SiP, and the carbide is one or more of Li2CO3, TiC, SiC, and B4C, add them to the above mixed solution and continue heating and stirring for 6-24 hours to obtain a SEI film solution; S3: Under ultraviolet light, the SEI film solution is evenly scraped on the substrate with a scraper, or evenly spin-coated on the substrate by setting a rotation speed to obtain a SEI film to be dried, and then transferred to a vacuum drying oven to dry to obtain a SEI film; S4: scraping or spin coating the mixed solution of S1 on the substrate according to the method of step (3), and then transferring it to a vacuum drying oven and drying it to obtain a polymer solid electrolyte membrane; S5: Transfer the SEI film prepared in S3 to the upper and lower surfaces of the polymer solid electrolyte membrane in step (4), assemble according to the battery assembly process and perform performance testing.

2. The method for preparing a multi-component SEI film according to claim 1, characterized in that: The polymer matrix is ​​preferably PVDF and PVDF-HFP.

3. The method for preparing a multi-component SEI film according to claim 1, characterized in that: The lithium salt is preferably LiTFSI and LiFSI.

4. The method for preparing a multi-component SEI film according to claim 1, characterized in that: The solvents are preferably DMF and NMP.

5. The method for preparing a multi-component SEI film according to claim 1, characterized in that: The mass ratio of the polymer matrix to the lithium salt is preferably 2:

1.

6. The method for preparing a multi-component SEI film according to claim 1, characterized in that: The stirring temperature is preferably 50° C., and the stirring time is preferably 12 h.

7. The method for preparing a multi-component SEI film according to claim 1, characterized in that: The fluoride is preferably LiF, the oxide is preferably Li2O, the boride is preferably LiBH4, the phosphide is preferably LiPO2F2, the carbide is preferably Li2CO3, and the mass ratio of the fluoride, oxide, boride, phosphide and carbide is preferably 2:0.5:1:1:0.

5.

8. The method for preparing a multi-component SEI film according to claim 1, characterized in that: The mass ratio of the total mass of the fluoride, oxide, boride, phosphide and carbide to the mass of the polymer matrix is ​​0.1-1.

9. The method for preparing a multi-component SEI film according to claim 1, characterized in that: The wavelength range of the ultraviolet lamp is 200-400nm, preferably 365nm, and the irradiation intensity is 5-20mW / cm 2 , preferably 10 mW / cm 2 .

10. A battery, characterized in that: A multi-component SEI film prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Artificial SEI film protection lithium negative electrode for lithium primary battery and preparation method of artificial SEI film protection lithium negative electrode

    CN116454282A

  • Bipolar artificial SEI (solid electrolyte interface) membrane for lithium metal negative electrode as well as preparation method and application of bipolar artificial SEI membrane

    CN117175035A

  • Composition, article, method of forming article, anode-free rechargeable battery and forming method thereof, and battery

    US20210020949A1